2018
DOI: 10.3390/nu10101503
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effect of the α-Amylase Inhibitor Albumin from Buckwheat (Fagopyrum esculentum Moench) on Postprandial Hyperglycaemia

Abstract: Inhibiting starch hydrolysis into sugar could reduce postprandial blood glucose elevation and contribute to diabetes prevention. Here, both buckwheat and wheat albumin that inhibited mammalian α-amylase in vitro suppressed blood glucose level elevation after starch loading in vivo, but it had no effect after glucose loading. In contrast to the non-competitive inhibition of wheat α-amylase inhibitor, buckwheat albumin acted in a competitive manner. Although buckwheat α-amylase inhibitor was readily hydrolysed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…In humans the digestion begins in the mouth with the α‐amylase enzyme which converts polysaccharides to monosaccharides . The inhibition of α‐amylase enzyme in the digestive system is one of the best options to maintain the postprandial glucose level . α‐amylase inhibitors significantly decrease the post‐prandial hyperglycemia in the treatment of T2DM .…”
Section: Introductionmentioning
confidence: 99%
“…In humans the digestion begins in the mouth with the α‐amylase enzyme which converts polysaccharides to monosaccharides . The inhibition of α‐amylase enzyme in the digestive system is one of the best options to maintain the postprandial glucose level . α‐amylase inhibitors significantly decrease the post‐prandial hyperglycemia in the treatment of T2DM .…”
Section: Introductionmentioning
confidence: 99%
“…Heat stability of α-amylase inhibitor has been shown by many studies. The inhibitor has been found to be stable at a temperature range of 40-90 º C 12,13 . The inhibitor is completely inactivated at 100 º C by boiling for 10 min 8 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies have also shown that rice bran protein hydrolysates do not affect α-glucosidase [14], and peptides from oat globulin can even promote αglucosidase activity [11,26]. Some cereals, such as wheat and buckwheat, contain proteins that inhibit αamylase [8]. Through enzymatic hydrolysis, cereal protein hydrolysates can produce α-amylase inhibitory activity [10,13,47].…”
Section: Carbohydrate Digestive Enzyme Inhibition Activitymentioning
confidence: 99%
“…In vivo animal experiments have been used to verify the efficacy of cereal and pseudocereal protein hydrolysates in maintaining blood glucose homeostasis (Table 3). Protein hydrolysates from buckwheat [8], wheat [8], rice [38], and corn [39,40] have directly alleviated the increase in blood glucose after meals caused by carbohydrate intake in normal rats. The mechanisms may be related to the inhibition of DPP-IV activity and the secretion of GLP-1 and insulin secretion.…”
Section: Maintaining Blood Glucose Homeostasis Via In Vivo Animal Expmentioning
confidence: 99%